2014
DOI: 10.1002/2012wr013320
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of regional hydroclimatic shifts: An analysis of changing hydrologic regimes

Abstract: Temporal shifts in precipitation and runoff regime curves appear throughout the continental United States, but differ from region to region. This paper explores these regime shifts by building upon a hydroclimatic classification system that partitions the United States into clusters of similarly behaved catchments using four simple hydroclimatic indicators. Hydroclimate data from over four hundred catchments over a 55 year period (belonging to the MOPEX data set) are analyzed to reveal how the indicators have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 64 publications
0
35
0
2
Order By: Relevance
“…However, the previous studies of drought propagation have not fully considered the effects of other climate characteristics, such as climate aridity and the timing of the precipitation within the year, on the propagation of droughts. Indeed, many studies of regional variations of catchment water balances have shown that climate aridity and the timing of precipitation with respect to potential evapotranspiration, as well as seasonality, can have a significant impact on both annual and seasonal water balances (Berghuijs et al, 2014;Coopersmith et al, 2014). For this reason, we present an extension of the drought propagation analysis by van Loon et al (2014) to include the effects of both climate aridity and the timing of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the previous studies of drought propagation have not fully considered the effects of other climate characteristics, such as climate aridity and the timing of the precipitation within the year, on the propagation of droughts. Indeed, many studies of regional variations of catchment water balances have shown that climate aridity and the timing of precipitation with respect to potential evapotranspiration, as well as seasonality, can have a significant impact on both annual and seasonal water balances (Berghuijs et al, 2014;Coopersmith et al, 2014). For this reason, we present an extension of the drought propagation analysis by van Loon et al (2014) to include the effects of both climate aridity and the timing of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The baseflow index (BFI), the ratio between the volume of baseflow and the volume of total streamflow, was originally recommended in the low flow studies (Institute of Hydrology, ) for indexing the effect of geology on low flows; however, the BFI now represents a general index of catchment hydrological response. Among various applications, BFI has been implemented as an index of river flow regime classification (Bejarano, Marchamalo, Garcia de Jalon, & Gonzalez del Tanago, ; Kennard, Mackay, Pusey, Olden, & Marsh, ; Olden, Kennard, & Pusey, ) and, as such, has also been used to detect hydrological regime changes along with other low flow indices (Coopersmith, Minsker, & Sivapalan, ; Crooks & Kay, ; Sawicz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mudelsee et al (2003) report that there is no upward trend in floods in a small number of large European rivers. Coopersmith et al (2014) described changes in hydrologic regimes, including flood events, for the continental United States. Hodgkins et al (2015) assessed 1204 reference and reference-like hydrometric stations in North America and Europe and found no compelling evidence of consistent changes in major floods over the past 80 years.…”
Section: Introductionmentioning
confidence: 99%